From musician of a viceroy to succentor in the Cathedral of Lima: Cristóbal de León (fl. 1561-1608) and other cleric musicians of his time - Vera Aguilera, Alejandro (2022)
Despite the increase in recent decades in our knowledge of colonial music, significant gaps remain about specific periods and places. Lima is perhaps the most striking of all of them because, despite being a colonial seat, we know relatively little about its musical life. This gap, however, is even more marked before 1612, when the constitutions of the music chapel of Lima Cathedral were promulgated. Since then, there is more information, at least in this institution, but we only have incomplete data for the previous period. Intending to help to remedy, in part, this lack, this paper studies a virtually unknown musician named Cristóbal de León. Through archival sources, we shall see that this subject developed a relevant musical activity in Lima from 1561 to 1608, which included the composition of chanzonetas and other works. In addition, he managed to enter the priesthood largely thanks to his musical profession, just as other cleric musicians did at the time. And he was probably related to the relevant musical activity of the monasteries of nuns in Lima during the 17th century.